Clozapine-Associated Myocarditis with Ventricular Fibrillation Revealing Brugada Syndrome: A Case Report - Maheu, Shanya; Masson, Violaine; Tadros, Rafik; Bahremand, Arash (Santé mentale au Québec)

(untitled) (Revue Santé mentale au Québec, 2026)
Clozapine is the gold-standard treatment for refractory psychotic disorders but is associated with rare, potentially fatal cardiovascular complications. We report the case of a 72-year-old man with schizoaffective disorder and complex multimorbidity who developed acute cardiac decompensation compatible with Clozapine-associated myocarditis. Despite prompt Clozapine discontinuation and supportive management, he experienced ventricular fibrillation leading to cardiac arrest. Subsequent investigations revealed a spontaneous Type I Brugada electrocardiogram (ECG) pattern compatible with Brugada syndrome (BrS), a rare inherited cardiac channelopathy associated with sudden cardiac death. After full medical stabilization and recovery of cardiac function, antipsychotic treatment was cautiously reintroduced with Quetiapine, resulting in good psychiatric response without recurrence of cardiac abnormalities to date. This case highlights the diagnostic challenges at the intersection of psychopharmacology and inherited arrhythmogenic disorders in older psychiatric patients. Moreover, it underscores the importance of considering Brugada syndrome in unexplained cardiac arrest and malignant arrhythmias during Clozapine treatment, even when myocarditis is initially suspected.